“Born with a silver spoon in the mouth has bad sides too”: Experimentally increasing growth rate enhances individual quality but accelerates reproductive senescence in females of the mealworm beetle, Tenebrio molitor - Crosland, Agathe; Rigaud, Thierry; Balourdet, Aude; Moret, Yannick (Frontiers in Ecology and Evolution, 2022)
Senescence occurs because of the decline of the strength of selection with age, allowing late-life reduced performances not being counter selected. From there, several phenomena may explain late-life reduced performances, such as the accumulation of deleterious mutations, the expression of pleiotropic genes or the existence of resource trade-offs between early and late performances. This latter phenomenon is at the core of the disposable soma theory of ageing, which predicts that growth and early-life reproduction have costs that increase reproductive and actuarial senescence. Whereas the impact of the cost of early reproduction on reproductive and actuarial senescence has been extensively studied, that of the cost of growth remains overlooked and often inconclusive, possibly because of confounding effects associated with the procedures used to manipulate growth rate. Here, we investigated the cost of growth rate and its impact on reproductive senescence and longevity of females of the mealworm beetle, Tenebrio molitor. For this purpose, we generated insects with contrasted growth rates by raising groups of them in conditions below, above and optimal relative humidity (RH: 55%, 85% and 70%, respectively) during the larval stage. The resulting adult females then bred, under the same optimal RH conditions, early in life, then later in life and were followed there until death. We found that larvae grown under the highest relative humidity exhibited the highest larval growth rate, thanks to both shorter growth duration and the achievement of heavier pupae mass. Adult females from this favorable growing condition lived longer, were more fecund early in life, but suffered from lower late-life reproductive investment. Our study shows that growth rate, which is highly dependent on the early-life environment, is an important factor modulating adult reproductive senescence, through the occurrence of early-late life trade-offs.